Achievement of selected A21SCDC actions for sustainability by South African contactors : a review (2002-2012) - Reyneke, Riané (2014)
Unfortunately, the detrimental impact of the built environment on the achievement of worldwide sustainability is enormous. Therefore, this study considers the progress made by the leading South African building contractors in achieving selected actions proposed in the Agenda 21 for Sustainable Construction in Developing Countries. William McDonough (2004) said: “Doing a bad thing less bad doesn’t make it good”. This research was driven by the search for true and effective changes in South Africa’s construction industry towards sustainability. In order to establish the progress being made by the construction industry it is necessary to look back and evaluate changes made. The “Big Five” construction contractors in South Africa were interviewed and completed a survey to establish what they have done and changed, within a ten year period, to operate more sustainable construction businesses. The main focus of the study is on contractors’ internal housekeeping and site operations. Internal housekeeping entails the drafting of strategic organisational plans, implementing sustainable organisational values and business conduct, reducing the organisational impact on the environment and efficient resource use in offices. Site operations entail environmentally aware construction practices, construction and demolition waste management and reducing the use of natural resources on sites